Corporate social performance and firm performance : Comparative study among developed and emerging market firms - Ting, Irene Wei Kiong; Noor Azlinna, Azizan; Bhaskaran, Rajesh Kumar; Sukumaran, Sujit K (MDPI, 2020)
This study examines the impact of firms' environmental, social and governance (ESG) initiatives on financial performance. It also compares the valuation effects of corporate social performance initiatives in developed and emerging market firms. The study was based on ESG ranking scores in the Thomson Reuters database, and the sample comprised 1317 emerging market firms and 3569 developed market firms. In comparison with developed market firms, emerging market firms had higher ESG combined scores, ESG Controversy scores, category scores of resources use, workforce, human rights and corporate social responsibility strategy scores. This study finds that stakeholder initiatives positively impact valuation effects, based on all sample results. Firm-generated controversies may decrease valuation effects in the stock market. Results indicated that ESG initiatives have a significant positive to the firm performance. The presence of independent board members and ownership by investors is a positive determinant for value creation. The adoption of best practice corporate governance principles is an important determinant of the valuation of firms. Firms' propensity to use defence mechanisms decreases valuation effects. Developed market firms received positive valuation effects due to ESG initiatives.